Comparsion of Activities of Fatty Acyl Desaturases and Elongases Among Six Teleosts With Different Feeding and Ecological Habits - Xie, Dizhi; Ye, Jialing; Lu, Meisong; Wang, Shuqi; You, Cuihong; Li, Yuanyou (Frontiers in Marine Science, 2020)
Fatty acyl desaturases 2 (Fads2) and elongases of very long chain fatty acid 5 (Elovl5) are two key enzymes involved in the biosynthesis of long-chain polyunsaturated fatty acids (LC-PUFA), and their activities determine the LC-PUFA biosynthetic ability of teleost. In order to investigate the relation of enzymic activities with fish’s feeding habits and ecological habits, the activities of Fads2 and Elovl5 were compared among six teleosts, namely, freshwater carnivorous mandarin fish (Siniperca chuatsi), freshwater herbivorous grass carp (Ctenopharyngodon idellus), marine carnivorous orange-spotted grouper (Epinephelus coioides), marine herbivorous rabbitfish (Siganus canaliculatus), anadromous Atlantic salmon (Salmo salar) and catadromous Japanese eel (Anguilla japonica). Among them, the enzymatic features of Fads2 and Elovl5 from the last five fish species have been characterized, while those of S. chuatsi were unknown. And thus, the coding sequences (CDS) of S. chuatsi fads2 and elovl5 (elovl5a and elovl5b) were isolated and their function were further characterized by heterologous expression in yeast. The results showed that S. chuatsi Fads2 has a monofunctional Δ6 desaturase, and Elovl5a has a higher activity towards C18-C20 PUFAs than that in Elovl5b, which showed noteworthy activity towards C22 PUFAs. The comparison of enzymatic activities among the six teleosts showed that the ∆6 Fad and Elovl5 activities varied markedly among fish species, especially, the activity of Δ6 Fad in C. idellus, S. canaliculatus, and A. japonica was significantly higher than that in S. chuatsi, S. salar and E. coioides. For C18 PUFA substrates, A. japonica Elovl5 has higher elongation than that in other tested fish, and exhibits higher activity towards the C20 PUFAs. The results suggest that the ∆6 Fad activity is influenced by both feeding habits and ecological habits, while the Elovl5 activity was more affected by the feeding habits. These data enrich our knowledge on LC-PUFA biosynthesis diversity of fatty acid desaturation and elongations in teleosts, and provide guidance for the choice of dietary PUFA precursors for farmed fish.